Depth of response may predict clinical outcome in patients with recurrent/metastatic head and neck cancer treated with pembrolizumab-containing regimens - Saijo, Ken; Imai, Hiroo; Ouchi, Kota; Sasaki, Keiju; Yoshida, Yuya; Kawamura, Yoshifumi; Taniguchi, Sakura; Kasahara, Yuki; Komine, Keigo; Shirota, Hidekazu; Takahashi, Masanobu; Ishioka, Chikashi (Frontiers in Oncology, 2023)
Background: Pembrolizumab-containing regimens are standards of care for recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). The depth of response (DpR) predicts the survival of patients with several types of solid cancers; however, its association with the survival outcomes of patients with R/M HNSCC treated with pembrolizumab-containing regimens remains unclear.Methods: This study included 66 patients with R/M HNSCC who received a pemblolizumabcontaining regimen as a first-line therapy at